Anthropometric Indicators as Predictors of Mortality in Early Life Among Low Birthweight Indian Infants - Choudhary, Tarun Shankar; Kumar, Mohan; Sinha, Bireshwar; Shaikh, Saijuddin; Mazumder, Sarmila; Taneja, Sunita; Bhandari, Nita (Frontiers in Nutrition, 2022)
Background Low birthweight (LBW) babies (<2.5 kg) are at higher risk of mortality and weight for height z score is currently recommended for identifying infants at risk of mortality. Objective To compare different anthropometric measures at 28-day of age in a cohort of LBW Indian infants for predicting mortality between 28-day and 180-day of age. Methods We used data from an individually randomized controlled trial of LBW infants weighing between 1,500 and 2,250 g. Sensitivity, specificity, positive, and negative likelihood ratios, positive and negative predictive values, and area under receiver operating characteristics curves (AUC) were used to estimate the discrimination of mortality risk. The Cox regression was used to estimate hazard ratios and population attributable fraction for each anthropometric indicator. These estimates were calculated for individual as well as combinations of anthropometric indicators at the cut-off of –2 and –3 SD of the WHO 2006 growth standards. Results Severe underweight (weight-for-age z-scores [WAZ] < –3) had a sensitivity of 75.0%, specificity of 68.0% with an AUC of 0.72. The risk of death was higher (HR 6.18; 95% CI 4.29–8.90) with a population attributable fraction of 0.63 (95% CI 0.52–0.72) for infants severely underweight at 28-day of age. Combination of different anthropometric measures did not perform better than individual measures. Conclusion Severe underweight (WAZ < –3) better discriminated deaths among LBW infants < 6 months of age. It can be considered for diagnosis of nutritionally at-risk infants in this age group. Clinical Trial Registration [ClinicalTrials.gov], identifier [NCT02653534].